Bone marrow mesenchymal stem cells alleviate smoke inhalation injury by regulating alveolar macrophage polarization via the CD200-CD200R pathway - Ding, Ziling; Zhuang, Yong; Zhao, Yunlong; Shi, Jie; Guo, Xiaoqin; Fan, Haojun; Lv, Qi (Frontiers in Immunology, 2025)
IntroductionSmoke inhalation injury (SII) is the most common cause of death in burn patients who are victims of fire. The inflammatory response to smoke inhalation is an important factor leading to acute lung injury (ALI) or acute respiratory distress syndrome (ARDS), so finding effective anti-inflammatory targets is the key to treating SII. Our previous study demonstrated that bone marrow mesenchymal stem cells (BMSCs) can regulate the M2-type polarization of alveolar macrophages, inhibit the inflammatory response, and have a good therapeutic effect on SII. However, the potential mechanism remains largely unknown. The immune checkpoint molecule CD200 is an important player in the immunomodulatory function of MSCs. However, whether CD200, as an immune molecule that targets macrophages, could be a new anti-inflammatory target for treating SII has not been reported.MethodsTo delineate the role of the immune checkpoint CD200 in this process, we employed an in vitro co-culture system of BMSCs and alveolar macrophages, employing siRNA-mediated knockdown to specifically inhibit CD200 expression in BMSCs. The effects of CD200 knockdown on macrophage polarization and associated molecular pathways were subsequently investigated. For in vivo validation, a rat model of smoke inhalation injury was established to evaluate the therapeutic efficacy of CD200-deficient BMSCs on lung injury and macrophage polarization.ResultsOur study revealed that BMSCs significantly promoted the M2-type polarization of alveolar macrophages. In contrast, the ability of BMSCs to promote the conversion of M1 to M2 macrophages was significantly diminished by knocking down CD200. These observations suggest that the regulatory effect of BMSCs on alveolar macrophage polarization is partly mediated through the CD200-CD200R pathway. Mechanistically, this regulation was associated with CD200-CD200R-mediated suppression of c-Jun N-terminal kinase (JNK) activity in alveolar macrophages. In vivo, we further confirmed that CD200 knockdown significantly downregulated the regulatory effect of BMSCs on M1/M2 macrophage polarization in rats with SII, which in turn attenuated the therapeutic effect of BMSCs on lung injury after smoke inhalation.DiscussionOur findings identify the immune checkpoint molecule CD200 as an anti-inflammatory target in the regulation of alveolar macrophages by BMSCs and provide new insights for more effective and precise MSC-based cell therapy.